2014
DOI: 10.1164/rccm.201310-1753oc
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Activity of the Tongue in Obstructive Sleep Apnea. A Novel Application of FDG Positron Emission Tomography Imaging

Abstract: Rationale: The metabolic activity of the tongue is unknown in patients with obstructive sleep apnea (OSA). Tongue electromyographic (EMG) activity is increased in patients with OSA. This increase in tongue EMG activity is thought to be related to either increased neuromuscular compensation or denervation with subsequent reinnervation of the muscle fibers. Increased glucose uptake in the tongue would support increased neuromuscular compensation, whereas decreased glucose uptake in the tongue would support dener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 69 publications
(101 reference statements)
0
23
0
Order By: Relevance
“…Boyd et al (2004) showed that inflammatory cells were increased in the muscular layer of patients with OSA, with CD4+ and activated CD25+ T cells predominating. In addition, the most recent study showed that glucose uptake in the GG of patients with sleep apnea was reduced in comparison with obese normal subjects with [18F]-2-fluoro-2-deoxy-D-glucose positron emission tomography imaging (Kim et al 2014b). Taken together, it can be reasonably assumed that the mechanism of down regulation of maximal strength of GG in the arousal state may be caused by the above-mentioned factors in OSA (Boyd et al 2004;Kim et al 2014b).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Boyd et al (2004) showed that inflammatory cells were increased in the muscular layer of patients with OSA, with CD4+ and activated CD25+ T cells predominating. In addition, the most recent study showed that glucose uptake in the GG of patients with sleep apnea was reduced in comparison with obese normal subjects with [18F]-2-fluoro-2-deoxy-D-glucose positron emission tomography imaging (Kim et al 2014b). Taken together, it can be reasonably assumed that the mechanism of down regulation of maximal strength of GG in the arousal state may be caused by the above-mentioned factors in OSA (Boyd et al 2004;Kim et al 2014b).…”
Section: Discussionmentioning
confidence: 96%
“…There have been the studies concerning muscular dysfunction of GG which resulted from inflammation, denervation and the metabolic change of muscular fibers (Boyd et al 2004;Kim et al 2014b). Boyd et al (2004) showed that inflammatory cells were increased in the muscular layer of patients with OSA, with CD4+ and activated CD25+ T cells predominating.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, poor airway mechanics can prevail in OSAS patients who appear to show adequate dilator muscle responsiveness, as determined by electromyogram recordings (Eckert and Wellman, 2015), and OSAS patients may be at risk of increased upper airway muscle fatigue . Structural changes in upper airway muscles of OSAS patients, including fibre type transitions (Stauffer et al, 1989;Smirne et al 1991;Series et al, 1995Series et al, , 1996aFerini-Strambi et al, 1998;Carrera et al, 2004) and altered metabolic activity (Series et al, 1995;Kim et al, 2014) are reported, consistent with evidence of altered isolated muscle function (Series et al, 1995(Series et al, , 1996a(Series et al, ,b, 1999Carrera et al, 1999Carrera et al, , 2004. Inflammation and myopathy (Boyd et al, 2004;Kimoff et al, 2011) have been described in upper airway muscle biopsies from OSAS patients, with evidence too of neuropathic sensorimotor injury in OSAS (Svanborg 2005;Saboisky et al, 2012).…”
Section: Obstructive Sleep Apnoea Syndrome: Neurogenic and Myogenic Mmentioning
confidence: 99%
“…Another possibility, however, is that repetitive collapse, injury, edema, and/or hypoxemia lead to progressive UA muscle dysfunction over time. Kim and colleagues used fluorodeoxyglucose positron emission tomography imaging to measure the metabolic activity of the tongue in more than 100 obese patients with and without OSA (12). Surprisingly, despite prior reports of increased EMG activity in those with OSA, the metabolic activity of the subjects with OSA was reduced compared with control subjects.…”
Section: The Upper Airway Musclesmentioning
confidence: 99%